Digital Transformation in the Public Sector: Study of the Implementation of the State Civil Service Information System in Makassar City - Sulmiah Sulmiah (Pinisi Journal of Social Science, 2024)
In a global context, digital transformation has emerged as a key catalyst in enhancing efficiency and transparency in public service, particularly through the use of state civil apparatus information systems. However, the implementation of such systems at the BKPSDMD of Makassar City faces significant challenges, especially related to integration, human resources, and technological infrastructure. This study aims to comprehensively analyze the implementation of the information system at the BKPSDMD of Makassar City, identify the obstacles encountered, and evaluate its impact on operational efficiency and service quality. A descriptive qualitative method was utilized, with data collected through interviews, observations, and document analysis. The findings indicate that a lack of skilled personnel and inadequate infrastructure are the main barriers, leading to suboptimal use of the information system. This study provides recommendations for improving policies and practices in public data management that can support the efficiency and transparency of local government. The conclusion of this research underscores the importance of investing in human resources and technological infrastructure to maximize the benefits of digital transformation in the public sector.